Self-Declare as an Implementation of Islamic Business Ethics and Its Relevance to Consumer Protection - Ainul Masruroh (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2023)
Although halal certification is mandated by Law Number 33 of 2014 concerning Halal Product Assurance, its implementation is difficult especially for micro and small businesses (MSMEs). Self-declaration provides a way for MSMEs, although there are concerns about the accuracy and consumer trust. This research examines the intersection between halal self-declaration, Islamic business ethics, and consumer protection. By using normative legal research, this study highlights the importance of monitoring the regulations of the Halal Product Assurance Law and ethical principles in ensuring halal integrity and protecting consumer rights. Self-declaration is in line with Islamic business ethics, emphasizing unity, justice, and honesty. This ensures consumer protection by prioritizing transparency and compliance with halal standards. Effective supervision by BPJPH, MUI, and other relevant institutions is necessary, as well as considering sanctions for businesses that do not comply. This is important to protect consumer rights and maintain halal integrity as stipulated in consumer protection laws.